More than this - Ness, Patrick, 1971- (Somerville, Massachusetts : Candlewick Press, 2013)
Awakening inexplicably in the suburban English town of his early childhood after drowning, Seth is baffled by changes in the community and suffers from agonizing memories that reveal sinister qualities about the world around him.
Keywords: Drowning -- Fiction; England -- Fiction; England -- Fiction; Dystopian fiction